PENINGKATAN KEMAMPUAN GURU BAHASA DALAM MENYUSUN RPP DENGAN MENGGUNAKAN METODE SUPERVISI AKADEMIK DI SMP - ., Eddy Abdullah (Jurnal Pembelajaran Prospektif, 2019)
This study aims to improve the ability of language teachers in creating lesson plans using academic supervision methods. Academic supervision is one of the principals' tasks in developing teachers through the supervisory function to solve educational problems, including problems faced by teachers simultaneously and not looking for teacher errors. The form of this research is the School Action Research (SAR), which uses a qualitative approach with descriptive methods. In this study consists of two cycles and carried out using academic supervision methods to improve the ability in creating lesson plans in Indonesian and English subjects. The data obtained are in the form of teacher observation sheets in teaching supervision activities. From the results of analysts it was found that the ability to create lesson plans for language teachers increased from cycle I and cycle II, namely, cycle I to Indonesian language teachers I (60%), Indonesian language teachers II (45%), English language teachers I (50%) and English teacher II (40%) and in cycle II there was an increase in Indonesian language teacher I (80%), Indonesian language teacher II (85%), English teacher I (90%) and English teacher II (75% ). The conclusion of this study is that academic supervision methods can improve the ability to create lesson plans in language teachers in Negeri 3 Matan Hilir Selatan.